Halal tourism: literature synthesis and direction for future research - Muhamad, Nur Sa'adah; Sulaiman, Syahnaz; Adham, Khairul Akmaliah; Said, Mohd Fuaad (Universiti Putra Malaysia Press, 2019)
Halal tourism, which arises from the growth in the number of Muslim travellers world-wide and the rapid development of halal industry, is defined as the engagement of any object or action by Muslim travellers that conforms to the Islamic teachings and facilitates the practice of the religion. As such, the application of halal concept in tourism, including in its development and marketing, must be guided by the Islamic principles. With the purpose to understand the current state of knowledge and practice, we reviewed the literature on halal tourism that has been published in high-tier academic journals. Based on the review, we identified the emergent themes and the knowledge gaps for future research. Among others, we found that the industry is booming with increased participations from Muslim-minority countries. However, there seems to be variations in the practice, perhaps due to the complexity of the market needs. The implementation of halal tourism by Muslim-minority countries is the most pressing issue due to the need to ensure that the process and the service offered strictly comply with the requirements of Islamic teachings, while at the same time, to ensure that the countries are able to develop their halal sectors into competitive industries. Understanding the implementation of halal tourism is an important agenda for future research to ensure that the service provided addresses the fundamental issue of Muslims' obligations to adhere to the Islamic teachings in all aspects of their lives including while travelling.